2007
DOI: 10.2298/pac0702075p
|View full text |Cite
|
Sign up to set email alerts
|

Historical materials from the medieval fortress Bac

Abstract: Conservation and restoration of cultural heritage are the objects of great interest worldwide. For setting the correct methodology for the procedures of the restoration it is very important to have the right information about the state of the object and the characteristics of the original materials. The basis of our examinations were clay products (samples of bricks, terracotta and clay roof tile) from the middle ages, the fortress in Bac. The following methods were used: x-ray diffraction, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 1 publication
0
8
0
1
Order By: Relevance
“…4 can be used for estimation of the fi ring temperature [4,24,25]. Th e thermal expansion method is based on the fact that when the partially fi red clay body is subjected to a linear heating during TDA, shrinkage occurs above a certain temperature.…”
Section: Fig 3 Th Ermogravimetry Of the Gothic (Gray) And Romanesqumentioning
confidence: 99%
“…4 can be used for estimation of the fi ring temperature [4,24,25]. Th e thermal expansion method is based on the fact that when the partially fi red clay body is subjected to a linear heating during TDA, shrinkage occurs above a certain temperature.…”
Section: Fig 3 Th Ermogravimetry Of the Gothic (Gray) And Romanesqumentioning
confidence: 99%
“…Ceramic objects are composed of a mixture of natural materials that are, by a variety of processes, transformed to a solid, brittle substance with high thermal resistance, high hardness and chemical stability. Ceramics played an important part in human lives throughout history [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. In the past, it was used for practical and decorative objects, as a structural material for buildings, aqueducts, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Ramos et al investigated the enamels of ceramic tiles from a heritage in the region of Valencia (Spain). Barone et al, [9], and Casaletto et al, [10] studied archeological ceramic artefacts found in different Italian sites, Coentro, [11] used multi-analytical methods for identification of pigment used in the 17th century Portuguese azulejos, and Pérez-Arantegui et al, [16] tested ancient cobaltblue-decorated ceramics from Aragon (Spain). Tite et al [21], Al-Saad [22], and Özçatala [24], investigated Islamic ceramics.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations